Activating Patients for Sustained Chronic Disease Self-Management - Cheryl J. Dye; Joel E. Williams; Janet H. Evatt (SAGE Publishing, 2016)
This article describes the impact of an 8-week community program implemented by trained volunteers on the hypertension self-management of 185 patients who were batch randomized to intervention or wait-list control groups. Compared with control group participants, a higher proportion of treatment group participants moved from the cognitive to behavioral stages of motivational readiness for being physically active ( P < .001), practicing healthy eating habits ( P = .001), handling stress well ( P = .001), and living an overall healthy lifestyle ( P = .003). They also demonstrated a greater average increase in perceived competence for self-management, F (1.134) = 4.957, P = .028, η 2 = .036, and a greater increase in mean hypertension-related knowledge, F (1.160) = 16.571, P < .0005, η 2 = .094. Enduring lifestyle changes necessary for chronic disease self-management require that psychosocial determinants of health behavior are instilled, which is typically beyond standard medical practice. We recommend peer-led, community-based programs as a complement to clinical care and support the increasing health system interest in promoting population health beyond clinical walls.